ANALISIS QIRA’AT SAB’AH DITINJAU DARI ILMU NAHWU PERSPEKTIF IMAM FAKHRU AR-RAZI - Hakmi Wahyudi; Hakmi Hidayat; Sri Wahyuni Hakim; Zulbaida Zulbaida; Widiarti Kamaruddin (Lembaga penelitian dan pengabdian kepada masyrakat, 2021)
The purpose of this research was to analyze qira'at sab'ah from the perspective of nahwu science from the perspective of Imam Fakhru Ar-Razi. This study used the Library Research research method. The data analysis uses content analysis. While the data sources that the authors use consist of primary data sources and secondary data. The results of the study show that there are seven different aspects of qir'at which are reviewed in terms of nahwu science including 1) Disputes over isim in the form of Mufrad, Mutsanna or Jama' and mudzakkar and Muannats, 2) Disputes in the form of 'Irab (sentence position), 3) Disputes regarding Tashrif (Patterns of Changes in word form), 4) Disputes about its location, earlier or later, this can occur in letters or words, 5) Disputes about changing letters or words, 6) Disputes about adding and subtracting lafadz, 7) Disputes about the form of dialect tarqiq or tafhim, vowel fathah or imalah, idzhar, hamza with vowel or tashil and others.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//